1993
DOI: 10.1093/bja/70.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Intubation After Induction of Anaesthesia With Profol, Alfentanil and I.V. Lignocaine

Abstract: We have assessed tracheal intubating conditions in 60 ASA I or II patients after induction of anaesthesia with propofol 2.5 mg kg-1 and alfentanil 10 or 20 micrograms kg-1 with or without i.v. lignocaine 1 mg kg-1. No neuromuscular blocking agents were administered. Patients were allocated randomly to four groups: group 1 = propofol-alfentanil 10 micrograms kg-1; group 2 = propofol-alfentanil 10 micrograms kg-1-lignocaine 1 mg kg-1; group 3 = propofol-alfentanil 20 micrograms kg-1; group 4 = propofol-alfentani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 0 publications
1
56
0
1
Order By: Relevance
“…We also found that propofol and fentanyl alone also provided unacceptable intubating conditions at 60 s in all patients, with a failure rate of 30% at the first attempt. Propofol has been shown in some studies to provide acceptable intubating conditions without the use of muscle relaxants; however, this is usually in combination with alfentanil and/or lignocaine, and not in a rapid-sequence induction technique [9,10]. Beck et al [11] claimed that propofol and alfentanil provided a satisfactory alternative to thiopentone and suxamethonium for a rapid-sequence induction; however, they did not apply cricoid pressure and used a fairly large dose of 50 mg.kg ¹1 of alfentanil.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that propofol and fentanyl alone also provided unacceptable intubating conditions at 60 s in all patients, with a failure rate of 30% at the first attempt. Propofol has been shown in some studies to provide acceptable intubating conditions without the use of muscle relaxants; however, this is usually in combination with alfentanil and/or lignocaine, and not in a rapid-sequence induction technique [9,10]. Beck et al [11] claimed that propofol and alfentanil provided a satisfactory alternative to thiopentone and suxamethonium for a rapid-sequence induction; however, they did not apply cricoid pressure and used a fairly large dose of 50 mg.kg ¹1 of alfentanil.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids are agents that suppress respiration in addition to providing appropriate conditions for endotracheal intubation; they are therefore good substitutes for muscle relaxants when used along with intravenous or inhaled hypnotics during intubation (1,2). Previous studies have examined the use of alfentanil for endotracheal intubation in children and adults without the use of muscle relaxants (5)(6)(7)(8)(9)(10). Remifentanil is an ultra-short-acting opioid resulting in short-term complications (11-13).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4-7 Propofol alone or in combinations with small (< 40 µg·kg -1) doses of alfentanil was more likely to be associated with suboptimal intubating conditions. 1,[4][5][6][7] Similarly, propofol in conjunction with < 3 µg·kg -1 of remifentanil was associated with suboptimal intubating conditions. 2 However, these studies employed multiple anesthesiologists for intubation.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7] The adjunctive administration of lidocaine 1 mg·kg -1 appears to reduce coughing during intubation. 5 Poor visibility during laryngoscopy can be subjective and is dependent on the experience of the anesthesiologist. However, additional administration of muscle relaxants improves visibility and success rate but comes at a price -myalgia.…”
Section: Discussionmentioning
confidence: 99%